Adipose-Derived Stem Cells in Bone Tissue Engineering: Useful Tools with New Applications. (6th November 2019) - Storti, Gabriele; Scioli, Maria Giovanna; Kim, Bong-Sung; Orlandi, Augusto; Cervelli, Valerio
Abstract : Adipose stem cells (ASCs) are a crucial element in bone tissue engineering (BTE). They are easy to harvest and isolate, and they are available in significative quantities, thus offering a feasible and valid alternative to other sources of mesenchymal stem cells (MSCs), like bone marrow. Together with an advantageous proliferative and differentiative profile, they also offer a high paracrine activity through the secretion of several bioactive molecules (such as growth factors and miRNAs) via a sustained exosomal release which can exert efficient conditioning on the surrounding microenvironment. BTE relies on three key elements: (1) scaffold, (2) osteoprogenitor cells, and (3) bioactive factors. These elements have been thoroughly investigated over the years. The use of ASCs has offered significative new advancements in the efficacy of each of these elements. Notably, the phenotypic study of ASCs allowed discovering cell subpopulations, which have enhanced osteogenic and vasculogenic capacity. ASCs favored a better vascularization and integration of the scaffolds, while improvements in scaffolds' materials and design tried to exploit the osteogenic features of ASCs, thus reducing the need for external bioactive factors. At the same time, ASCs proved to be an incredible source of bioactive, proosteogenic factors that are released through their abundant exosome secretion. ASC exosomes can exert significant paracrine effects in the surroundings, even in the absence of the primary cells. These paracrine signals recruit progenitor cells from the host tissues and enhance regeneration. In this review, we will focus on the recent discoveries which have involved the use of ASCs in BTE. In particular, we are going to analyze the different ASCs' subpopulations, the interaction between ASCs and scaffolds, and the bioactive factors which are secreted by ASCs or can induce their osteogenic commitment. All these advancements are ultimately intended for a faster translational and clinical application of BTE.